2012
DOI: 10.1155/2012/568567
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Xenografts of Non Small Cell Lung Cancer: Resurgence of an Old Model for Investigation of Modern Concepts of Tailored Therapy and Cancer Stem Cells

Abstract: Current chemotherapy regimens have unsatisfactory results in most advanced solid tumors. It is therefore imperative to devise novel therapeutic strategies and to optimize selection of patients, identifying early those who could benefit from available treatments. Mouse models are the most valuable tool for preclinical evaluation of novel therapeutic strategies in cancer and, among them, patient-derived xenografts models (PDX) have made a recent comeback in popularity. These models, obtained by direct implants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 60 publications
2
64
0
2
Order By: Relevance
“…Recent studies have suggested that PDX models might hold great promise for testing novel drug candidates as well as to identify rational combination therapies (17). Among the arguments made for PDX models is that they may be expected to provide a better representation of within tumor heterogeneity and also that they would reflect the relevant human components of the tumor microenvironment better (Table 1).…”
Section: Limitations Of Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that PDX models might hold great promise for testing novel drug candidates as well as to identify rational combination therapies (17). Among the arguments made for PDX models is that they may be expected to provide a better representation of within tumor heterogeneity and also that they would reflect the relevant human components of the tumor microenvironment better (Table 1).…”
Section: Limitations Of Mouse Modelsmentioning
confidence: 99%
“…Several reports also describe the loss of human stromal cells within the first few passages after engraftment (17,21), which raises the question of the possibility of species incompatibility with respect to human tumor-mouse microenvironment interactions. This is emphasized by the results of Hylander and colleagues (22), who showed that by the first passage of PDX tumors, the stroma and vessels supporting their growth are of murine origin (22).…”
Section: Limitations Of Mouse Modelsmentioning
confidence: 99%
“…PDX were established from primary lung cancers from patients undergoing surgical resection, who gave their informed consent and expanded as previously described (18).…”
Section: Animal Studiesmentioning
confidence: 99%
“…18) and clinical samples, we phenotypically characterize and functionally prove the existence of a novel subset of CICs, regulated by the microenvironment, driving lung tumor dissemination and metastasis and we identify CXCR4 signaling as a potential target for novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…We addressed the capacity of TF-011-MMAE to inhibit the growth of tumors with heterogeneous target expression using PDX models, which are thought to represent the heterogeneity that exists between human tumors (31)(32)(33). Immunohistochemical (IHC) analysis of xenografted primary human tumor biopsies confirmed heterogeneity of tissue factor expression, and seven PDX models were selected on the basis of variable levels of tissue factor expression.…”
Section: Tissue Factor Humab and Tf-adcs Efficiently Induce Adcc In Vmentioning
confidence: 99%